Transformation of Pesantren Academic Traditions (A Study of Ma'had Aly Learning Innovations) - Riswadi, Riswadi; Amrullah, Zen (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Learning in pesantren or Islamic boarding school is often identified with backward learning, old-fashioned thinking, and an inability to respond to current developments. Ma'had Aly Sukorejo Situbondo dismissed this view. The presence of Ma'had Aly broke the barriers of backwardness that had been running in the pesantren. This article examines the transformation of Ma'had Aly's academic tradition through its learning innovations. This study used a qualitative approach, the type of field research, and data collection techniques in the form of interviews, observations, and documentation. The analysis technique is formulated through the described data categorization and the interpretation of the data acquired through the theories used in this study. The results of this study show that Ma'had Aly Sukorejo Situbondo has transformed its education through learning innovation, combining the teacher-centered and student-centered approaches by developing learning methods in the form of al-Ta'lim wa Al-Tadris, structured assignments, dialogues, lectures, and general stadiums. In reviewing the books in the curriculum, Ma’had Aly Sukorejo provides the broadest possible opportunities for teachers to learn with various learning innovations. From the perspective of innovation, Ma'had Aly has adopted Neo-Modernism thinking. The learning strategies include textual, contextual, comparative, Maqasidiyah, and Naqdiyah. This study has implications for the scientific development of pesantren education in general and pesantren higher education in particular, that the tradition of thinking in pesantren is from stagnant to critical (dynamic) thinking.